A Detail Process for CAD Based Breast Cancer Detection (Journal of Cancer Research Updates, 2019)
Breast cancer is known to cause high mortality unless detected in time. Early detection during the onset of the disease can prevent mortality. Early detection can prevent the spreading of the disease thus providing a healthy life to senior citizens. Mammographic screening and surgical biopsy will yield huge number of images to be deciphered by radiologists and pathologists respectively. MIAS dataset is sufficiently large to conduct experimental analysis. Moreover, the dataset contains 322 mammogram images of different size, shape and morphology. This paper discussed about breast cancer detection and diagnosis process. (Word count -91 words).